Penerapan Aplikasi Pemesanan Tiket Online Terhadap Jumlah Penumpang Kereta Api - Schouten, Femmy Sofie; Agus Triani, Ririn (Universitas Muhadi Setiabudi, 2023)
This study aims to analyse the positive impact of online ticket booking application on the number of train passengers based on ticket sales data. The development of technology has changed the paradigm in the transport industry, especially trains, by introducing online ticket booking application services. The analysis method used is a non-parametric statistical test to measure the relationship between the application and the number of railway passengers. Ticket sales data for several years before and after the implementation of the app were used in this study. The results of the analysis show a positive relationship between the application and the increase in the number of passengers, suggesting that the ease of access and convenience in booking tickets through the application has encouraged more people to use the railway service. Although these results indicate a positive impact, the study recognises the existence of other factors that may affect the number of passengers. This study recommends that railway operators continue to develop and improve online ticket booking applications as part of their marketing and customer service strategies. This research contributes to the understanding of how technology shapes consumer behaviour in the transportation industry and the extent of its impact on train passenger numbers. These results can guide decision makers in optimising the application of technology in the transportation industry.